Unprecedented energy storage in metal-organic complexes via constitutional isomerism - Kottaichamy, Alagar Raja; Deebansok, Siraprapha; Deng, Jie; Nazrulla, Mohammed Azeezulla; Zhu, Yachao; Bhat, Zahid Manzoor; Devendrachari, Mruthyunjayachari Chattanahalli; Vinod, Chathakudath Prabhakaran; Kotresh, Harish Makri Nimbegondi; Fontaine, Olivier; Thotiyl, Musthafa Ottakam (Chemical Science, 2023)
The essence of any electrochemical system is engraved in its electrical double layer (EDL), and we report its unprecedented reorganization by the structural isomerism of molecules, with a direct consequence on their energy storage capability. Electrochemical and spectroscopic analyses in combination with computational and modelling studies demonstrate that an attractive field-effect due to the molecule's structural-isomerism, in contrast to a repulsive field-effect, spatially screens the ion-ion coulombic repulsions in the EDL and reconfigures the local density of anions. In a laboratory-level prototype supercapacitor, those with beta-structural isomerism exhibit nearly 6-times elevated energy storage compared to the state-of-the-art electrodes, by delivering similar to 535 F g(-1) at 1 A g(-1) while maintaining high performance metrics even at a rate as high as 50 A g(-1). The elucidation of the decisive role of structural isomerism in reconfiguring the electrified interface represents a major step forward in understanding the electrodics of molecular platforms.